Biochar Input to Saline-Alkali Farmland Can Improve Soil Health and Crop Yield: A Meta-Analysis - Liqiang Zhang; Baoyin Bate; Jinhu Cui; Yudi Feng; Jianning Yu; Zhengguo Cui; Hongyu Wang; Qiuzhu Li (Agriculture)
Soil salinization in farmland is a critical factor limiting global soil health, food security, and ecosystem productivity. Biochar has recently shown great application potential in agricultural fields in many domains, such as soil structure improvement, carbon sequestration, and reductions in greenhouse gas emissions. Here, a meta-analysis of 113 published papers was carried out to quantify the effects of biochar on the remediation of saline-alkali soil and crop yield in terms of climatic conditions and agricultural management, with the aim of determining the optimal agricultural management strategy for biochar application to saline-alkali soils. The results show that adding biochar to saline-alkali farmland increases the TOC in soil (44.0%) and water utilization efficiency (8.7%), and decreases soil salinity (−9.6%), certain salt ion contents in particular (Na+, 12.5%; Cl−, 23.4%; HCO3−, −17.7%), along with soil pH (−2.2%), resulting in a 20.8% higher crop yield. Applying shell biochar at a rate of 10–20 t·ha−1 for monoculture is the most promising way to bolster the yield in severely saline-alkali irrigated farmland. However, adding biochar raises CO2 and CH4 emissions by 9.8% and 31.6%, respectively, but lowers the emission of N2O by 29.4%. These findings provide scientific recommendations for the sustainable application of biochar in saline-alkali farmland areas worldwide.